Developing a Pricing Mechanism for Electric Vehicle Charging Stations in Sri Lanka - Kamburugamuwage, Hasnaka; Shukri, Mohamed (Journal of Engineering Issues and Solutions, 2025)
Electric vehicle (EV) charging infrastructure/ service development is identified as a critical area to assist the expected rapid uptake of EVs in Sri Lanka. Optimal pricing of these services is necessary to ensure the sustainability of EV industry including EV owners and Charge point operators. The pricing of EV charging services is currently not regulated in Sri Lanka. Therefore, various tariff structures and rates within a wide range is observed. The cost of public charging stations is generally categorized as operational costs, energy costs and capital costs. Pricing structures set for recovering these costs are identified to be based on three main types of Time based, Energy based or Fixed fee. This study proposes two pricing structures of ‘Energy based pricing structure’ and ‘Energy and time-based pricing structure’ for EV charging service in Sri Lanka. The tariff rate calculation for each structure is described. Further, the tariff structures are comparatively analysed to evaluate the suitability of these to be adopted in Sri Lanka.